2010
DOI: 10.1186/1472-6963-10-6
|View full text |Cite
|
Sign up to set email alerts
|

Simple versus composite indicators of socioeconomic status in resource allocation formulae: the case of the district resource allocation formula in Malawi

Abstract: BackgroundThe district resource allocation formula in Malawi was recently reviewed to include stunting as a proxy measure of socioeconomic status. In many countries where the concept of need has been incorporated in resource allocation, composite indicators of socioeconomic status have been used. In the Malawi case, it is important to ascertain whether there are differences between using single variable or composite indicators of socioeconomic status in allocations made to districts, holding all other factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Household socioeconomic status (SES) was defined based on a composite index of permanent household income indicators. This method has been widely used to characterize SES in lower income countries where income and educational level may not adequately capture the full extent of an individual’s socio-economic status [ 25 - 27 ]. Principal components analysis (PCA) was performed on data assessing ownership of assets such as refrigerators, washing machines, mobile phones, chairs, tables, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Household socioeconomic status (SES) was defined based on a composite index of permanent household income indicators. This method has been widely used to characterize SES in lower income countries where income and educational level may not adequately capture the full extent of an individual’s socio-economic status [ 25 - 27 ]. Principal components analysis (PCA) was performed on data assessing ownership of assets such as refrigerators, washing machines, mobile phones, chairs, tables, etc.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Variables with low standard deviations tend to carry low weights, such that items that were routinely present or absent had less influence on differentiating SES among households. 25 Each household was assigned an aggregate SES scores.…”
Section: Methodsmentioning
confidence: 99%
“…Since there is no uniform cut-off point for multimorbidity across studies, both two or more and three or more conditions are common criteria [3]. Also, rates of prevalence were found to be higher in primary-care based study populations than in samples drawn from the general population [4], and may depend on the number of conditions taken into consideration [5]. In a German study based on claims data from a large sample, van den Bussche et al [6] found a prevalence of 62.1% for multimorbidity, defined as three or more conditions, among subjects aged 65 years or older and a mean number of 5.8 chronic conditions among these multimorbid subjects.…”
Section: Introductionmentioning
confidence: 97%